The animated pocket dictionary of respiratory diseases ([Singapore] : Focus Medica, 2011)
The FOCUS Animated Pocket Dictionary of Respiratory Diseases, the first ever animated dictionary in the subject, fills that void quite effectively. A must-have resource for physicians and students who would greatly benefit from this module, it covers related terms and definitions. All the definitions have been described with breathtaking, state of the art 3D animations.
A-W.
Keywords: Respiratory tract diseases; Lung diseases; Respiratory organs -- Diseases; Dictionary; Electronic books; Dictionaries